Biallelic JAK1 mutations in immunodeficient patient with mycobacterial infection - Davide Eletto (Nature Portfolio, 2016)
JAK1 mediates intracellular signalling from multiple cytokine receptors. Here, Elettoet al. identify JAK1 mutations that disrupt multiple signalling pathways and are associated with primary immunodeficiency, atypical mycobacterial infection susceptibility and early-onset metastatic bladder carcinoma.